Size-dependent shape distributions of platinum nanoparticles. Issue 18 (26th August 2022) - Ding, Ruikang; Padilla Espinosa, Ingrid M.; Loevlie, Dennis; Azadehranjbar, Soodabeh; Baker, Andrew J.; Mpourmpakis, Giannis; Martini, Ashlie; Jacobs, Tevis D. B.
Abstract : Transmission electron microscopy revealed size-dependent shape distributions in platinum nanoparticles, which were consistent with trends observed by applying Boltzmann statistics to the energy computed with atomistic models. Abstract : While it is well established that nanoparticle shape can depend on equilibrium thermodynamics or growth kinetics, recent computational work has suggested the importance of thermal energy in controlling the distribution of shapes in populations of nanoparticles. Here, we used transmission electron microscopy to characterize the shapes of bare platinum nanoparticles and observed a strong dependence of shape distribution on particle size. Specifically, the smallest nanoparticles (<2.5 nm) had a truncated octahedral shape, bound by 〈111〉 and 〈100〉 facets, as predicted by lowest-energy thermodynamics. However, as particle size increased, the higher-energy 〈110〉 facets became increasingly common, leading to a large population of non-equilibrium truncated cuboctahedra. The observed trends were explained by combining atomistic simulations (both molecular dynamics and an empirical square-root bond-cutting model) with Boltzmann statistics. Overall, this study demonstrates experimentally how thermal energy leads to shape variation in populations of metal nanoparticles, and reveals the dependence of shape distributions on particle size. The prevalence of non-equilibrium facets has implications for metal nanoparticles applications from catalysis to solar energy.